Mechanism of Improving Aspirin Resistance: Blood-Activating Herbs Combined With Aspirin in Treating Atherosclerotic Cardiovascular Diseases - Zhao, Yixi; Yang, Shengjie; Wu, Min (Frontiers in Pharmacology, 2021)
Atherosclerotic thrombotic disease continues to maintain a high morbidity and mortality rate worldwide at present. Aspirin, which is reckoned as the cornerstone of primary and secondary prevention of atherosclerotic cardiovascular diseases (ASCVDs), has been applying in clinic extensively. However, cardiovascular events remained occur even though people utilize aspirin appropriately. Therefore, the concept of aspirin resistance (AR) was put forward by scholar, which is of great significance for the prediction of clinical outcome of disease. The pathogenesis of AR may incorporate with low patient compliance, insufficient dose, genetic polymorphism, increased platelet transformation, inflammation, and the degenerative changes and calcification of platelet. The improvement of AR in the treatment of ASCVDs has gradually become a research hotspot in recent years. Traditional Chinese medicine (TCM) regards individuals as a whole and treats them from a holistic view, which has been found to have advantages in clinical studies on the treatment of AR. Many kinds of blood-activating TCM have the effect of improving AR. The potential mechanism for the improvement of AR by blood-activating herbs combined with aspirin was explored. The combination of blood-activating herbs and aspirin to improve AR is likely to turn into a hot topic of research in the future.